Comments to paper by N. Kumar et. al. on CaBiGdNbVO9 - Tomaszewski, Paweł E. (Journal of the Korean Physical Society, 2025)
The lead-free material CaBiGdNbVO9 described in the paper Kumar et al. (J Korean Phys Soc, 85:451–539, 2024) does not exist, but is a result of erroneous processing of diffraction data. The studied samples were mixtures of several other compounds, mainly GdVO4. KCI Citation Count: 0